Sebuah Hubungan antara motivasi belajar bahsa inggris dengan penguasaan kosakata - Nana Noviana; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2023)
This study aims to analyze the form of correlation between students’ motivation in learning English and vocabulary mastery at the eighth grade students of SMP N 7 Surakarat in the 2022/2023 academic year. The researcher used the quantitative method. The research gave a questionnaire consisting of 30 items and vocabulary test to gather the data. The finding of this study indicated that there is a positive correlation between students’ motivation in learning English and vocabulary mastery. It is proven by the result of the calculation of rxy 0.556 > rtable in the significance 5% (0.361) and 1% (0.463). Then it could be concluded that the alternative hypothesis (Ha) is therefore deemed to be accepted and the null hypothesis (Ho) is rejected. In this research, it could be concluded that there is a positive correlation of the research between students’ motivation in learning English and students’ vocabulary mastery. That means the motivation in learning English has an impact, the better students’ vocabulary mastery. Key words: Motivation in learning English, Vocabulary mastery, Correlation study